Molecular mechanisms influencing the efficiency of RNA interference in the European corn borer, Ostrinia nubilalis (Lepidoptera: Crambidae) - Cooper, Anastasia M. W. (Kansas State University, 2020)
RNA interference (RNAi) pathways function in endogenous gene regulation and protection against viruses and transposons in eukaryotic organisms. The exogenous RNAi mechanism has been utilized as a powerful reverse genetics tool to analyze gene function. In addition, RNAi-based pest management strategies are now emerging; however, applications are limited due to inefficient results for some insects, especially lepidopterans. The European corn borer (ECB), Ostrinia nubilalis, is an agriculturally relevant lepidopteran pest that exhibits very low RNAi efficiency but has a great need for new control strategies that utilize novel modes of action. This dissertation research seeks to investigate molecular mechanisms influencing RNAi efficiency in ECB and determine if commonly used reagents and tactics can improve RNAi efficiency in this species. The specific objectives were: 1) to investigate double-stranded RNA (dsRNA) stability in larval gut contents and hemolymph in ECB, 2) to identify and characterize dsRNA-degrading nuclease genes from ECB, 3) to identify and characterize core RNAi pathway genes from ECB, and 4) to compare strategies for enhancing RNAi efficiency (nanoparticles, transfection reagents, and nuclease inhibitors) in ECB. Ex vivo incubation experiments showed that dsRNA was degraded in ECB gut contents and hemolymph under physiologically relevant pH conditions. Sequencing revealed transcripts for four dsRNA-degrading endonuclease (OndsRNase) genes and one RNAi efficiency-related nuclease (OnREase) gene in ECB. Expression analysis indicated that OnREase, OndsRNase2, and OndsRNase4 might impact oral RNAi efficiency in ECB, whereas OnREase and OndsRNase1 may impact injection RNAi efficiency. Sequencing also revealed a single transcript for Dicer 2 (OnDcr2), R2D2 (OnR2D2), and Argonaute 2 (OnAgo2). Expression analysis indicated that each of these core RNAi pathway genes were expressed in all ECB developmental stages and tissues investigated. Ex vivo incubation experiments showed that Metafectene Pro, chitosan-based nanoparticles, EDTA, and Zn²⁺ enhanced dsRNA stability in ECB gut contents and hemolymph, but Lipofectamine RNAiMax, Co²⁺, and Mn²⁺ did not. Surprisingly, improving dsRNA stability did not increase RNAi efficiency in ECB in vivo. Ingestion, injection, and tissue culture-based RNAi assays indicated that most target genes and all ECB developmental stages investigated were highly refractory to RNAi. These findings suggest that multiple mechanisms, including instability of dsRNA, deficient core RNAi machinery, and refractory target genes, likely contribute to low RNAi efficiency in ECB. Primary outcomes of this project included an in-depth investigation of dsRNA instability under physiological conditions in ECB tissues, a preliminary identification of candidate dsRNA-degrading nuclease genes that likely contribute to dsRNA instability in ECB, a foundational characterization of core RNAi pathway genes presumed to participate in the exogenous RNAi response of ECB, and a detailed comparison of numerous strategies for enhancing dsRNA stability and potentially RNAi efficiency in ECB. Overall, results from this research support that multiple mechanisms likely contribute to RNAi inefficiency in lepidopteran insects. This investigation will help improve RNAi efficiency in lepidopteran insects, so effective RNAi-based pest management strategies can be developed.
Keywords: RNA interference; Insect bioassays; Double-stranded RNA stability; Nucleases; Core RNAi pathway genes; Target genes